Constitutive behaviour study of BaxK1−xFe2As2 iron-based superconducting powder. (1st April 2023) - Xia, Xi; Zhu, Yanchang; Zhu, Chundong; Han, Meng; Liu, Cong; Wang, Dongliang; Zhang, Xianping; Ma, Yanwei
Abstract: In order to simulate the preparation process of Ba x K1− x Fe2 As2 (BaK-122) iron-based superconducting (IBS) wires and tapes and formulate appropriate forming process for practical production, it is very important to study the constitutive behaviour of BaK-122 IBS powder. However, there is little research on this aspect at present. In this paper, the constitutive behaviour of BaK-122 powder was investigated. The modified Drucker–Prager cap (DPC) model was introduced to describe the constitutive behaviour of BaK-122 powder. Uniaxial compression test, radial compression test and mould pressing test were carried out to determine the material parameters. Furthermore, the numerical simulation of pressing forming of BaK-122 powder and drawing process of BaK-122 IBS wires were carried out through the finite element simulation method. These results demonstrated that the simulations were in good agreement with the experimental results, which verified the accuracy of the model. The first proposal of this mode lays a foundation for further simulating the preparation process of BaK-122 IBS wires and tapes to guide the actual production.